Corporate affairs and the conquest of social performance in mining. Issue 3 (July 2020) - Kemp, Deanna; Owen, John R.
Highlights: Social and environmental complexity is increasing and incidents continue to occur. Calls for meaningful corporate social responsibility in mining are fast escalating. Organisational structure is a central factor in meeting social and legal obligations. Social performance is currently stranded within corporate governance structures. Corporate affairs filter and control what is brought before company decision-makers. Abstract: Against a vast backdrop of regulation, and increasingly strong calls for industry change, major social and environmental incidents in mining continue to occur. There is resistance among major companies to the idea that restructuring their organisations will have any positive effect on their social performance. Our interest is in whether the structural positioning of social performance enables or prevents companies from governing their social and legal obligations. This includes the commitment to do no harm. Internal turf wars between social performance and corporate affairs reflect the difficulties that mining company executives confront in attempting to maintain production and contain corporate self-interest. What manifests structurally is a clear representation of how companies make sense of their priorities and the priorities of others. That companies would seek to limit inquiry into their own governance structures is even more reason to investigate.